Eksplorasi Konformitas Internalisasi: Sudut Pandang Peserta Didik Terhadap Perbedaan Gender - Wisda rahmadinur (Ikhtisar: Jurnal Pengetahuan Islam, 2023)
This research began with the condition of students who still did not have internalization of conformity to school regulations. Basically, every student has a different awareness of obeying school regulations. There are those who do it because of self-awareness, there are also those who are afraid of behaving and obeying school rules. The research method used is qualitative research with a case study approach. The population of this study was 25 students of class VIII MTsN 02 Padang Pariaman. The analysis used is data reduction, data display, verification and conclusions. The research instruments used were observation and interviews. The research results showed that male students smoked during recess, even though they had never smoked before. However, in order to be accepted by their group, they end up smoking. Meanwhile, when interviewed by female students, it was found that if they did not have an Android cellphone, it was as if they were foreigners. So the attitude that emerges in students is to make themselves included in blind conformity, namely the attitude of imitation solely because of prestige or wanting to be recognized for their existence. The implications of this research are intended to be taken into consideration in creating guidance and counseling programs. Keyword: Conformity; Internalisation; Gender